Giving voice to values how to speak your mind when you know what's right - Gentile, Mary C. (Yale University Press, 2010)
Based on interviews and current research in management and social psychology, this book weaves together illustrative stories--notably often positive exemplars--with specific guidelines and a tested methodolgy for preparing ourselves to plan, script, and execute effective strategies for implementing our values in times of ethical conflict. Unlike most books about business ethics, the focus of GVV is post-decision making (a phrase coined by Carolyn Woo, the dean of Notre Dame University's business school to describe the approach). It is not about deciding what the right thing to do is, but rather about how to get it done.